Diagnostic tools and staging of malignant pleural mesothelioma. (October 2015) - Powers, Amy; Carbone, Michele
The diagnosis of malignant pleural mesothelioma remains challenging and should be based on both histologic evidence of invasion and immunohistochemical findings supportive of mesothelioma. Cytology is a controversial method of diagnosis, but may be a useful tool, particularly in the identification of other metastatic malignancies. Malignant pleural mesothelioma must be differentiated from benign, reactive mesothelial proliferations and other metastatic malignancies. Histologic analysis in conjunction with immunohistochemistry, electron microscopy, and limited molecular diagnostics are most useful in establishing a diagnosis. The staging of malignant pleural mesothelioma is most commonly performed using a TNM (tumor, node, metastasis) system proposed by the International Mesothelioma Interest Group.